2013
DOI: 10.5398/medpet.2013.36.3.185
|View full text |Cite
|
Sign up to set email alerts
|

GHRH|HaeIII Gene Polymorphism in Dairy and Beef Cattle at National Livestock Breeding Centers

Abstract: ABSTRACT), kecuali pada sapi FH di BIB Lembang, sapi Brahman, dan Angus di BET Cipelang. Nilai heterozigositas tertinggi adalah 0,471 untuk sapi FH pejantan di BIB Lembang, sebaliknya, nilai terendah adalah 0,344 untuk sapi FH pejantan di BBIB Singosari. Nilai heterozigositas sapi FH lebih rendah daripada sapi Simmental dan Limousin. Gen GHRH pada sapi FH dan sapi pedaging menunjukkan polimorfik, kecuali pada sapi Brahman yang hanya memiliki alel B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…The GHRH|HaeIII locus or the GHRH g.4474 C>A SNP re-sulted in three genotypes, i.e., AA genotype by 3 bands (312, 94, and 45 bp), CC genotype by 4 bands (194, 118, 94, and 45 bp), and AC genotype by 5 bands (312, 194, 118, 94, and 45 bp). These three genotypes were consistent to the results reported by previous study (Rini et al, 2013).…”
Section: Ghrh G4474 C>a Snp Polymorphismsupporting
confidence: 93%
See 3 more Smart Citations
“…The GHRH|HaeIII locus or the GHRH g.4474 C>A SNP re-sulted in three genotypes, i.e., AA genotype by 3 bands (312, 94, and 45 bp), CC genotype by 4 bands (194, 118, 94, and 45 bp), and AC genotype by 5 bands (312, 194, 118, 94, and 45 bp). These three genotypes were consistent to the results reported by previous study (Rini et al, 2013).…”
Section: Ghrh G4474 C>a Snp Polymorphismsupporting
confidence: 93%
“…The same results were reported on this genetic polymorphism of HF cattle from the two AI centers and an ET Center providing a very rare of the AA (4.5%) cattle than the AC cattle (37.1%) and CC cattle (58.4%); likewise generating a very low A allele (22.5%) rather than C allele (77.5%) (Rini et al, 2013). Some previous studies also confirmed the same results for the lowest AA animals compared to the AB (AC) and BB (CC) animals, such as in Polish Holstein i.e., 7.8% vs. 33.9% and 58.3%; abd Jersey i.e., 3.2% vs. 42.7% and 54.1% (Szatkowska et al, 2009).…”
Section: Ghrh G4474 C>a Snp Polymorphismsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar frequencies of rare GHRH A allele, 0.2480 and 0.2400 were reported by Dybus and Grzestak (2006) and Klauzinska et al (2004), respectively. Further, frequencies for the GHRH A and GHRH B allele vary considerably between breeds, GHRH A allele was found to be lowest in cattle breeds such as the Hereford (Moody et al, 1995), Holstein (Kmiec et al, 2007;Szatkowska et al, 2009;Rini et al, 2013), Jersey (Szatkowska et al, 2009), Simmental and Limousin (Rini et al, 2013;Dybus et al, 2003). In contrast to those breeds, GHRH A allele frequency was found to highest in Angus cattle (Moody et al,1995;Rini et al, 2013), whereas the GHRH B allele was found with a maximum frequency in Brahman breed which originates from Bos indicus (Rini et al, 2013).…”
Section: Restriction Patterns With Haeiii Endonucleasementioning
confidence: 99%